Entrepreneurship Education a Panacea to Youth Unemployment - Ogunmayi Bamidele; Aribisala Oluwadamilare Olufolarin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The evolution and advancement of any nation lies on the originality of people which to a great extent, relates to the quality of training and entrepreneurship education in that nation. Such evolution and advancement lies on the creation of employed youths and per capital income enhanced. The inclusion of Entrepreneurship education in Nigeria tertiary curriculum in 2005 was to establish the entrepreneurship spirit and culture among graduates due to them depending on white collar jobs. Entrepreneurship nurtures social, economic well-being and economic growth by providing substantial openings for youth making them employed. Youth unemployment affects developing countries, Nigeria inclusively. Data was gotten through questionnaire given to youths between the ages of 18-40. Simple random sampling and stratified random sampling technique was deployed in selecting Two hundred and twenty youths which comprises of youths within Akoka environment and Entrepreneurs within Akoka, Lagos, Nigeria were administered questionnaire while one hundred and eighty seven questionnaires was gotten. Findings revealed that after several entrepreneurship seminars and inclusion of Entrepreneurship education in the curriculum, youth still prefer to do several immoralities and cybercrime to make a living. It was concluded that entrepreneurship education to be more equipped to make youths accept it rather than creating the fear of the unknown which makes them go for other bad social vices in creating wealth